Inquiry Based Science Education and Getting Immediate Students’ Feedback about Their Motivation - Kekule, Martina; Zak, Vojtech; Jeskova, Zuzana; Kimakova, Katarina; Ganajova, Maria; Kires, Marian (Scientia in educatione, 2017)
The paper is based on collecting evidence of the Establish project impact on students. For the purpose two questionnaires based on the existing tools have been used. Questionnaire 1 is a part of Intrinsic Motivation Inventory (IMI) based on the Self-determination theory. It is aimed at assessing students’ interests, their perceived choice and usefulness of implemented learning units and should be answered after each learning unit/several IBSE activities. Several items of CLES questionnaire are included there as well. Questionnaire 2 assesses the impact on students’ attitudes towards science and technology and on their knowledge about nature of building up science knowledge. Both questionnaires exist in the lower and upper secondary school versions. The paper presents selected data and results which were obtained by addressing the Questionnaire 1, so that the focus is on getting students’ feedback about their intrinsic motivation. Our assumption is that active learning is associated with positive intrinsic motivation of students. That is why we find as very important that educators have a possibility to understand the phenomenon more deeply. We aim to present the reliable tool for getting the feedback and to present a way of data processing which does not need advanced statistical methods, so that teachers (as well as science education researchers) can use and analyze data obtained by the tool. Means and standard deviations for items of the subscales Interest/Enjoyment, Perceived choice and Value/Usefulness were computed. To determine the consistency of results, the Standard Pearson correlation cofficient was computed for all items within the subscales. Based on the findings, we can conclude that participants’ answers (questionnaire results) were consistent (not responded mechanically).